Public Debt in Developing Countries : Has the Market-Based Model Worked? - Gill, Indermit; Pinto, Brian (World Bank, Washington, DC, 2012)
Over the past 25 years, significant levels of public debt and external finance are more likely to have enhanced macroeconomic vulnerability than economic growth in developing countries. This applies not just to countries with a history of high inflation and past default, but also to those in East Asia, with a long tradition of prudent macroeconomic policies and rapid growth. The authors examine why with the help of a conceptual framework drawn from the growth, capital flows, and crisis literature for developing countries with access to the international capital markets (market access countries or MACs). They find that, while the chances of another generalized debt crisis have receded since the turbulence of the late 1990s, sovereign debt is indeed constraining growth in MACs, especially those with debt sustainability problems. Several prominent MACs have sought to address the debt and external finance problem by generating large primary fiscal surpluses, switching to flexible exchange rates, and reforming fiscal and financial institutions. Such country-led initiatives completely dominate attempts to overhaul the international financial architecture or launch new lending instruments, which have so far met with little success. While the initial results of the countries' initiatives have been encouraging, serious questions remain about the viability of the model of market-based external development finance. Beyond crisis resolution, which has received attention in the form of the sovereign debt restructuring mechanism, the international financial institutions may need to ramp up their role as providers of stable long-run development finance to MACs instead of exiting from them.